Material culture: a digital documentation of the art and culture of the Saribas Malay, Sarawak - Faridah Sahari,; Rahah Hj Hasan,; Terry Lucas,; Nur Farziana Angat,; Zahraa Farhana Hasbi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper investigates the use and application of material culture study methods to document and organise the cultural collections of the Saribas Malay community in Betong Division, Sarawak. The main objective of the study is to identify the Saribas Malays’ awareness on the importance to document material culture. A documentation template based on material culture theory was designed to preserve and sustain cultural objects, starting with a practical application can be easily used and effectively implemented by the local community. This qualitative research used in-depth interviews to gather data on respondents’ awareness on the importance of documenting material culture and their perception on using the template. The respondents were selected among Saribas Malays who make, use, keep and collect cultural objects. For the purpose of this study, Fleming’s (1974) and Prown’s (1982) models were adapted to construct a template to document information of the artefacts and as analytical tools. The findings from the interview sessions with the Saribas community showed that they were positive towards the effort to preserve material culture through documentation. The simple template proposed was sufficient to record basic information of the artefacts. Although this will take a while to complete, but in the end, this activity will be able to document the artefacts and be used as reference for academics, museum cataloguing and antique collection purposes.